Self-service technologies (SSTS) and customer satisfaction in Banking industry - Sia, Chiew Lan. (Universiti Malaysia Sarawak (UNIMAS), 2013)
This paper aims to investigate the relationships between factors affecting self-service technologies (SSTs) in banking institutions with the customer satisfaction and later the impact of customer satisfaction of the SSTs usage. The 250 respondents from Kuching area participated in this survey. This study more concern on customer's perspective to identify the factors and impacts of SSTs usage. This due to fact that there are many predictors that lead to SSTs usage and also SSTs usage will contribute to vary of results.